2011
DOI: 10.1111/j.1465-3362.2011.00343.x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of drinkers views of health information and warning labels on alcohol containers

Abstract: There are high levels of public support for health information and warning labels on alcohol beverages. This study contributes much needed empirical guidance for developing alcohol beverage labelling strategies in an Australian context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(78 citation statements)
references
References 10 publications
8
68
0
2
Order By: Relevance
“…While there is evidence from the warning label literature to suggest that high-risk drinkers are more likely to receive and recall information provided on a label (Greenfield, Graves, & Kaskutas, 1993), it is unlikely that the impact SDLs have on awareness and knowledge of SDs will be sufficient to bring about immediate positive changes in drinking behaviors (Thomson et al, 2012). Changing drinking patterns can be a very complex process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is evidence from the warning label literature to suggest that high-risk drinkers are more likely to receive and recall information provided on a label (Greenfield, Graves, & Kaskutas, 1993), it is unlikely that the impact SDLs have on awareness and knowledge of SDs will be sufficient to bring about immediate positive changes in drinking behaviors (Thomson et al, 2012). Changing drinking patterns can be a very complex process.…”
Section: Discussionmentioning
confidence: 99%
“…A consistent finding across all qualitative research components was that SDLs are unlikely to be effective in influencing drinking behaviors in isolation, particularly for youth. SDLs need to be supported by educational campaigns and a comprehensive policy package that include controls on price and alcohol availability (Jones & Gregory, 2009;European Commission & CIROC, 2011;Loxey et al, 2004;Thomson et al, 2012).…”
Section: Mixed-methodsmentioning
confidence: 99%
“…However while many studies have been conducted to analyse consumer response to nutritional labelling on other food products and the effects of nutrition label format, consumers' interest and preferences to wine nutritional labelling is rarely investigated [9][10][11][12]. Results from these studies are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed even if these studies reveal the strong interest expressed by consumers to the inclusion of nutritional information on wine label, others demonstrate that the same inclusion may have both potential benefits and unintended consequences [3]. Thomson et al (2012) [12] showed that community strongly support for a range of information that could potentially be mandated on alcoholic beverages labels included nutritional information.…”
Section: Introductionmentioning
confidence: 99%
“…liver cirrhosis, brain damage etc.) is high (Thomson, Vandenberg, & Fitzgerald, 2012). Knowledge of the link between alcohol and cancer, however, is poor, and therefore consumers may be inadvertently putting themselves at risk (Benedetti, Parent, & Siemiatycki, 2009).…”
Section: Introductionmentioning
confidence: 99%